Students’ Choice of Dining Outlets during the COVID-19 Pandemic: What did Students Consider? - Noble Amoako Sarkodie; Edwina Asamoah; Jane Dery; Charlotte Gyimah; Comfort Gyeduaa (E-Journal of Humanities, Arts and Social Sciences)
The study investigated factors influencing tertiary students’ choice of dining outlets amidst the COVID-19 pandemic with its concomitant challenges and restrictions in Ghana. A cross-sectional survey was employed using a simple random sampling technique through a lottery to select 222 final-year students from Sunyani Technical University. A questionnaire was employed to gather data from respondents. The findings of the study conveyed that all the factors investigated are influential to students’ choice of dining outlets. The study further established that the gender of the students significantly influenced their choice of dining whilst age did not influence students’ choice of dining outlets. It is envisaged that the study would be beneficial to the government, hospitality operators, and hospitality educators as it contributes to providing a deeper insight into current factors that influence students’ choice of eatery during the heat of covid-19 pandemic. This study recommends that hospitality operators should focus more on the “cleanliness of serving wares equipment as well as all the areas examined to attract consumers in the study area. By complying with these recommendations, it is hoped that hospitality operators will become more competitive and will be able to meet the needs of their customers.